THE INFLUENCE OF USING ANDROID-BASED SAC MEDIA WITH THE STAD TYPE COOPERATIVE LEARNING MODEL ON STUDENTS LEARNING OUTCOMES AND INTEREST IN CHEMICAL BONDING MATERIAL - Pakpahan, Debora; Silaban, Ramlan; Nurfajriani, Nurfajriani; Nainggolan, Bajoka; Simatupang, Lisnawaty (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2024)
This research aims to determine the effect of using Android-based Smart App Creator media with the STAD type cooperative learning model on students' learning outcomes and interest in chemical bonding material. The research was carried out from September to December 2023 at SMA Negeri 1 Silima Pungga-Pungga. This research uses a test instrument in the form of multiplechoice questions with 20 questions and a non-test in the form of a learning interest questionnaire with 30 statements. The sampling technique used in this research is random sampling, namely random sampling. The research sample was students in classes X-1 and X-6, totaling 36 people in each class. Hypothesis I test uses the right-sided t-test with the research results obtained by the value tcount > ttable, namely 5,36 > 1,666. Hypothesis II test uses the right-sided t-test with the research results obtained tcount > ttable, namely 11,57 > 1,666. Hypothesis Test III uses a correlation formula with the research results obtained rcount > rtable, namely 0,547 > 0,339. Based on the research results, it can be concluded that there is a significant influence on students' learning outcomes and interest in learning using Android-based Smart App Creator media with the STAD type cooperative learning model on chemical bond material and there is a relationship between students' learning interest and student learning outcomes taught using the media. Android-based Smart App Creator with a STAD type cooperative learning model on chemical bonding material.